일부지역 저소득층 독거노인의 영양소 섭취, 영양위험도 및 생화학 지표에 관한 조사연구 - 김화영(Hwa-Young Kim); 김명환(Myung-Hwan Kim); 홍성길(Seong-Gil Hong); 황성주(Sung-Joo Hwang); 박미현(Mi-Hyoun Park) (Korean journal of community nutrition, 2005)
This purpose of this study was to investigate the nutrient intake, the health status as determined self-assessment checklist, biochemical indicators of elderly Korean women. We interviewed and 55 female subjects living alone in the Urban aged over 65 years. Information on their dietary intake was collected by 24-hour Recall method. Their health status was determined by a NSI checklist. Biochemical indicators were performed in whole blood and plasma of subjects. Except for protein, Fe, all of the elderly subjects belonged to over moderate nutritional risk. The average daily nutrient intake of the elderly was below the level of the recommended dietary allowances (RDA) for Koreans. A relationship between their health risk score and nutrient intake was observed negatively (not significantly). They had a risk of anemia as hemoglobin and hematocrit of subjects were under the normal value. Therefore, the reason that health risk score and health status badly was thought for lower nutrient intake.